PENGARUH KUALITAS PELAYANAN PANTAI PADANG-PADANG BALI TERHADAP KEPUASAN WISATAWAN NUSANTARA - Putri Sihotang, Heldi; Suwena, I Ketut; Sudiarta, I Nyoman (Jurnal IPTA (Industri Perjalanan Wisata); Vol 12 No 1 (2024): Jurnal IPTA (July 2024)DO - 10.24843/IPTA.2024.v12.i01.p07, 2024)
One of the interesting natural attractions in Bali is the beach, Bali is very famous for its beautiful beaches. One of the beach tourist destinations in South Badung which is the choice of archipelago tourists to visit is Padang-Padang beach in Pecatu which is located between hills and steep rocks, and stone stair caves to reach the white sand beach, which characterizes this beach. This study aims to determine the quality of service and the effect of service quality on the satisfaction of domestic tourists on Padang-Padang beach, Bali. This study uses qualitative and quantitative data analysis techniques with simple linear regression analysis. Sampling technique with purposive sampling method with 85 respondents. Data collection techniques with observation, interviews, documentation, literature study and questionnaires via google form and directly. The results showed that service quality has a significant effect on the satisfaction of domestic tourists. The results of service quality influence the satisfaction variable, which is 52,2%, and the other 47,8% is influenced by other factors outside the service quality variable not examined by the researcher. The service quality of Padang-Padang Bali beach is classified as good, but the Empaty dimension has the lowest percentage among other dimensions.